Isolasi senyawa flavonoid dari daun bakung (Crinum asiaticum L.) - Abadi, Hafizhatul; Rumanti, Ruth Mayana; Andry, Muhammad; Nasution, Muhammad Amin (Journal of Pharmaceutical and Sciences, 2023)
Introduction Sprains and fractured bones are treated with spider lily leaves (Crinum asiaticum L.). Alkaloids, flavonoids, tannins, steroids, and triterpenoids are among the chemical components found in spider lily leaves. The most significant phytochemicals in plants with wide biological advantages for humans are bioactive flavonoids. The purpose of: The study aimed to isolate flavonoid components from spider lily leaves. Methods: This study was descriptive, using the following steps: plant material collection and preparation, sample processing, simplicia characterization, extract preparation, phytochemical screening, hydrolysis, fractionation, analysis using paper chromatography (KKt), and compound isolation using preparative paper chromatography. The isolates were tested for purity using one-way and two-way KKt, and they were identified using UV-Vis spectrophotometry with a shear reagent. The results: The results of the characterization showed that the water content was 7.21%, the water-soluble extract was 11.21%, the ethanol-soluble extract was 9.23%, the total ash content was 1.99%, and the acid-insoluble ash content was 0.81%. The screening findings indicated the presence of flavonoid chemicals. The KKt analysis results revealed that the best mobile phase was 5% acetic acid with ammonia vapor specks, and the preparative KKt isolation results yielded a single blue isolate, which was then identified by UV-Vis spectrophotometry using a shear reagent, resulting in maximum wavelength absorption (max) at band II of 253nm, presumably identifying the isoflavone group of flavonoids. Conclusion: The conclusion showed the ethyl acetate fraction of spider lily leaves could be separated using paper chromatography and that identification by spectrophotometry UV-Vis using a shear reagent wasolate, which was assumed to be an isoflavone group component.